Maternal Clinic Attendance : Does Husbands' Knowledge about Pregnancy and Childbirth have Influence on Intra-Household Decision-Making? - Mpawenimana, Abdallah Saidi; Bassoumah, Bougangue; Yusuf Sani, Abubakar (Academic Research Publishing Group, 2018)
Husbands are very influential in making decisions for maternal healthcare, and the quality and type of decision depend on the level of understanding of maternity. This study explores how husbands' knowledge about key signs of pregnancy and childbirth translates into wives' involvement in decision-making and the type of decisions made towards care-seeking. These qualitative data were generated from individual interviews involving thirty husbands whose spouses were receiving maternity care in the Yendi Municipality of the Northern Region of Ghana. Purposive and quota sampling were used to reach the participants. Irrespective of husbands' knowledge about maternity, cultural beliefs and traditional gender role expectations had a far-reaching effects on wives' involvement in decisionmaking and the type of decisions made towards care-seeking. Though most husbands with adequate knowledge about maternity were more liberal by involving their wives and respecting their views in the decision-making process, others tended to be more conservative by considering decision-making as men's space. Most decisions were individualistic and male-centred. Healthcare promotion programmes should be directed towards changing the mindset of men about cultural beliefs and gender roles in relation to maternity care. There should be provision of education on pregnancy and childbirth and the associated benefits and dangers to equip men on how to recognise pregnancy-related complications to enable them to reach informed decisions for care-seeking.